LANGUAGE FUNCTION ON DJENAR MAESA’S AYU LITERARY WORK, ENTITLED “JANGAN MAIN-MAIN (DENGAN KELAMINMU)” - ANASTASIA, REBEKA RINDA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Short story is one of many ways to distribute language and is used to tell something or convey the hidden message. When language is performed, there must be discourse. Discourse does not emphasize in grammar, but focus on the meaning and coherence. It means there is relationship between discourse and literary work. The purpose of this research is to find out the use of language function. The wtiter does not only focus on the analysis of each sentence in the short story, but also to find out the interpretation. The writer selected Djenar Maesa Ayu’s literary work, entitled “Jangan Main-Main (dengan Kelaminmu)”, read the book thoroughly, and find language function and the interpretation itself. The results of the research show that there are many other functions of language. Each short stories contains different numbers of language function. “Jangan Main-Main (dengan Kelaminmu)” dominated by Emotive Function, “Mandi Sabun Mandi” dominated by Phatic Function, “Moral” dominated by Emotive Function, “Menyusu Ayah” dominated by Referential Function, and “Saya adalah Seorang Alkoholik” not dominated by any language function. Language Function facilitate the reader in understand the story, find a message that is implied, categorizes sentences according to its function and its interpretation.   Kata Kunci : analisa wacana, fungsi bahasa, pemilihan kata.